2013
DOI: 10.1111/ggi.12071
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of the cognitive, behavioral and physical status of day care service users with dementia: Factors associated with long‐term day care use

Abstract: It is better to control behavioral and psychological symptoms in order to improve the utilities of day care for dementia patients. The caregiving environment of dementia patients might be associated with the length of day care attendance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
4
1
Order By: Relevance
“…It was difficult to clarify the relationship between the caregiving system and LDC. Our previous report showed that sons and daughters‐in‐law were factors promoting long‐term day‐care use . The differences in the results between this study and previous reports may be due to the differences of the participants and/or analytic methods.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…It was difficult to clarify the relationship between the caregiving system and LDC. Our previous report showed that sons and daughters‐in‐law were factors promoting long‐term day‐care use . The differences in the results between this study and previous reports may be due to the differences of the participants and/or analytic methods.…”
Section: Discussioncontrasting
confidence: 83%
“…Our previous report indicated that dementia, as measured by ASSD scores checked by caregivers, influenced LDC . Another report showed that a low initial ASSD score was a factor in prolonging day‐care use . In this study, multivariate analysis showed that ASSD scores were related to LDC for each sex.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…We did not find studies specifically comparing the effects of DC and HC services on changes in cognitive and physical functions as well as behavioral symptoms of PWD. Nevertheless, previous studies have demonstrated that DC services can have a positive impact on health and well-being of PWD 19,23,30 and caregivers. 25,31 We observed that behavioral symptoms improved in both groups after 1 year of receiving services in the comparison of matched cohorts, even though the difference between the two groups was not significant.…”
Section: Discussionmentioning
confidence: 67%
“…We did not find studies specifically comparing the effects of DC and HC services on changes in cognitive and physical functions as well as behavioral symptoms of PWD. Nevertheless, previous studies have demonstrated that DC services can have a positive impact on health and well‐being of PWD and caregivers …”
Section: Discussionmentioning
confidence: 96%